Effect of Silane Addition on Chitosan-Fly Ash/CTAB as Electrolyte Membran - Isnaeni, Diana; Kusumastuti, Ella; Sulistyaningsih, Triastuti (Indonesian Journal of Chemical Science, 2017)
Electrolyte membrane was composed of chitosan and fly ash wich was modified using cetyl trimetil ammonium bromide (CTAB and silane had been done successfully. This research aims to determine the best membrane based on mechanical properties, proton conductivity, methanol permeability, and membrane selectivity. The steps consist of silica preparation from fly ash, modification of silica surface with CTAB, silica coupling process with GPTMS, synthesis of membranes, and membrane characterization. The result showed the best membrane produced by membrane with 10% silane addition with tensile strength 23,10 Mpa, elongation at break 3,17%, modulus young 6,72 Mpa, proton conductivity 8,00 x 10-4 S/cm, methanol permeability 3,37 x 10-7 cm2/s, and membrane selectivity 2,12 x 103 S s/cm3. The Fourier Transform Infra Red (FT-IR) membrane analysis result showed that only occured physical interaction and Scanning Electron Microscopy (SEM) analysis showed the distribution of particle wa spread evently and there was not agglomeration.